The victimizing effect of violent socialization: Intimate partner use of coercive sexual practices transnationally - Delaney, Aimée X. (International journal of offender therapy and comparative criminology, 2024)
Research seems to focus more on examining predictors of sexual victimization rather than violent experiences predicting coercive sexual behaviors. Little research explores victim to offender associations. The present study expands current literature by exploring transnational differences in which coercive sexual behaviors manifest from childhood violence experiences. Do experiences of violence during childhood impact the use of coercive sexual behaviors? Multilevel modeling regression analysis, used on data from the International Dating Violence Study, reveal several interesting findings: (1) violent socialization from families is associated with coercive sexual behavior, (2) violent socialization from the community is associated with coercive sexual behavior, and (3) nations where violent socialization is more prevalent, the average level of coercive sexual behaviors tends to increase. Identifying predictive processes for sexual coercion is important. Sexual coercion may be represented in subtle day to day interactions that over time instill a sense of violence normality and further perpetuate victimization.